Spatial Analysis on Determinant Reducing Regional Disparity in Java - Duwi Yunitasari; Ahmad Fauzan; Fajar Wahyu Prianto (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2023)
Regional disparity is one of the challenges faced by Indonesian government in developing Indonesia. Indonesian government has a focus on increasing equitable development with by increasing physical and non-physical connectivity through the 2015-2019 RPJMN III. In another hand, the allocation of capital or investment between regions can trigger or reduce regional disparity. This study aims to determine the role of technology, transportation infrastructure, and investment spatially in reducing regional disparity in Java. The place and time of this study are 6 provinces of Java in 2015 – 2019. The method used in this study was spatial econometric analysis. The spatial model used is Moran's I, Lagrange Multiplier Test, and Spatial Error Model (SEM) using Geoda 1.20 software. The results pf Moran’s I showed that there is a negative spatial dependence on regional disparity with a Moran index of -0.021. Based on the result of LM Test, the spatial model used is SEM. The estimation results of SEM model showed that technology has spatially a negative and significant impact on regional disparity in Java, while transportation infrastructure and investment has spatially a positive and significant effect on regional disparity in Java.